Society Perception Toward Flood Prevention in Sentosa Klang Park Selangor Malaysia - Fitria, Ceri; Amalia, Faza (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this research was to analyze public perceptions of flood prevention, the effects of floods, and the factors that caused flooding in Sentosa Klang park Selangor Malaysia. This type of research is descriptive qualitative using literature review technique, observation, interview, and documentation studies in data collection. The types of data used are primary data and secondary data obtained from Malaysian literature review. Primary data is collected by conducting interview with informants and making observation or open observation related to people's perception of flood prevention that occurred in Sentosa Klang park, Selangor Malaysia. Search via the internet is related to flood information, as well as document that have been published by relevant agencies. The results of the research found by the authors indicate that the Malaysian Government has adopted a policy for flood prevention but has not gone well. Factors of flooding in Sentosa Klang park, Selangor Malaysia due to changes in land use, lack of water catchment area, small and clogged drainage channel, lack of public awareness of the surrounding environment, and lower topography. The impact that is often felt by the post-flood population is skin disease, dengue fever, odor, and material losses.